Avaliação do hidrolisado hemicelulósico da casca de jabuticaba para a obtenção de xilitol por Candida guilliermondii - (:unkn) unknown (Universidade Estadual de Goiás, 2013)
Lignocellulosic materials, such as jabuticaba peel are sources of low cost with potential bioprocesses. The hemicellulose fraction of these materials can be hydrolyzed using dilute acids, with the release of xylose that is a substrate for biotransformation in xylitol. In this study was evaluated the capacity of production of xylitol from jabuticaba peel. Initially jabuticaba peel was washed several times with water until no more impurities. After this procedure the residue was subjected to drying in an oven at 60 º C for 24 hours and ground with a Wiley mill to 60 mesh. The material obtained was subjected to Soxhlet containing hexane to remove extractable. The free of extractable residue was dried at 100 ° C for 6 hours and subjected to hydrolysis with 1% sulfuric acid, 120 ° C and 1 atm at 1:10 (m/v) for 30 and 60 minutes to obtain two hydrolyzates. Analysis of sugars in both hydrolyzates showed no significant differences in sugar composition and thus the hydrolyzate 60 minutes was used for fermentation. The chemical composition of the hydrolyzate was used for fermentation: cellobiose 0.51 gL-1, glucose 2.64 gL-1; xylose 3.02 gL-1; arabinose 3.27 gL-1; xylitol 0.00 gL-1; glycerol 0.04 gL-1; formic acid 0.001 gL-1; acetic acid 0.14 gL-1. Was used for fermentation the yeast Candida guilliermondii in cells with two concentrations of 0.1 gL-1 and 0.2 gL-1 kinetics of production of sugars which ranged from 0 to 21 hours of fermentation. Under these conditions yielded a xylose consumption and conversion efficiency of 61.71 % in the fermentation with 0.1 gL-1 and 67.86 % of cells in the fermentation with 0.2 gL-1 of cells Candida guilliermondii, with a productivity volume of 0.56 and 0.62 g / L and the conversion yield of 0.15 and 0.16 gL-1 in 0.1 and 0.2 gL-1 yeast cells, respectively. It was noted that ethanol production was elevated to 21 h of fermentation ethanol concentration of 9.73 gL-1 and 9.04 gL-1 cell concentration of 0.1 gL-1 and 0.2 gL-1 respectively. The bioconversion of xylose to xylitol with hydrolyzate of jabuticaba peel proved to be a promising material for obtaining xylitol and ethanol.
Keywords: Aproveitamento de subprodutos; Conversão biotecnológica; Myrciaria cauliflora; Utilization of by-products; Biotechnological conversion; Myrciaria cauliflora; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA